Beyond the pollution haven hypothesis: Where and why do e-waste hubs emerge and what does this mean for policies and interventions?. Issue 98 (January 2019) - Davis, John-Michael; Akese, Grace; Garb, Yaakov
Abstract: Initial, and still dominant, explanations of transboundary e-waste flows have relied on the Pollution Haven Hypothesis (PHH), which theorizes that pollution intensive economic activities will relocate to jurisdictions with the most relaxed environmental regulations. This hypothesis has influenced the parameters of the BAN Amendment to the Basel Convention, which uniformly restricts the movement of hazardous waste (including e-waste) from the global North-to-South. Recent research, however, has shown that e-waste does not simply flow to less regulated areas with cheaper labor: for example, flows are not simply from North-to-South, and e-waste processing areas are only in a subset of developing countries and very specific regions within these. Specifically, e-waste processing tends to be done very largely within "hubs, " regional concentrations of firms and organizations, which, though overwhelmingly informal, exhibit many of the characteristics of other kinds of industrial clusters. Thus, a more nuanced theory of e-waste destinations is overdue, promising greater explanatory power as well as more granular and effective policy stances and tools. This paper contributes to these goals by synthesizing indications from the literature on e-waste hubs in Africa and Asia of recurring factors shaping their emergence, and further elaborating these on the basis of our own extensive field research in two very different informal e-waste hubs in Palestine and Ghana. This analysis offers an initial theory of place-specific characteristics and circumstances that attract and facilitate the emergence and agglomeration of such industries. Our findings thus allow us to move beyond the PHH first pass macro conceptualizations to more nuanced and dynamic accounts of e-waste destinations at a regional and even micro-level, as well to challenge and improve upon the policies derived from the PHH framing.